Simulation for Optimizing the Hybrid System of Solar Power Plant (SPP) and Diesel Power Plant (DPP) at Balang Lompo Island - Yunus, A.M. Shiddiq; Saini, Makmur; Fuad, M. Syaiful; Isradianto, Isradianto (Politeknik Negeri Ujung Pandang, 2020)
Balang lompo Island is supplied by Diesel Power Plant (DPP) and Solar Power Plant (SPP), in the operation of SPP it is considered not optimal due to the amount of solar panel capacity of 200 kWp while MPPT capacity of 120 kW and inverter capacity of 100 kVA, with these conditions the research was carried out with the aim of optimizing the generating system on Balang Lompo Island. The optimization of the generating system is conducted by simulation using Homer Legacy Beta software. By entering several important parameters such as technical, economic, and environmental factors therefore, the simulation results obtained in the form of the most optimal system operating patterns represented by one of the smallest net present cost (NPC) parameters, and also the recommended operating hours between DPP and SPP. The research method employed are the preliminary study research, identification and formulation of problems, data collection, data processing using Homer Legacy v2.81 Beta software, and analysis of the simulation results. In this study there are two conditions are compared, the first condition is the existing condition with an MPPT capacity of 120 kW and an inverter capacity of 100 kVA and the second condition is the addition of MPPT capacity to 200 kW and an inverter capacity of 200 kVA. Based on the results, it can be concluded that with the addition of capacity in SPP equipment, namely MPPT capacity to 200 kW and inverter capacity to 200 kVA, it is proven to be able to save NPC costs, O&M costs, fuel costs, reduction in DPP operating hours and DPP fuel consumption. With an NPC value of US 3,362,929 (IDR. 48,957,520,382), with the implementation of this system the NPC cost savings could reach US 197,161 (IDR. 2,870,269,838) during the 25-year operating period, and savings in US fuel/HSD consumption costs 23,936 (IDR. 348,460,288) per year.